The Variational Homotopy Perturbation Method for Solving ((n×n)+1) Dimensional Burgers’ Equations - F. A. Hendi; B. S. Kashkari; A. A. Alderremy (Journal of Applied Mathematics)
The variational homotopy perturbation method VHPM is used for solving n-dimensional Burgers’ system. Some examples are examined to validate that the method reduced the calculation size, treating the difficulty of nonlinear term and the accuracy.